Clusters of elements for quality assurance of health worker protection measures in times of COVID-19 pandemic - Bartosz Orzeł; Radosław Wolniak (Administrative Sciences, 2021)
The COVID-19 (coronavirus disease) pandemic has had a significant impact on the healthcare delivery system worldwide. Many pre-pandemic norms, standards, and methods of providing medical services in most medical facilities had to be changed and re-evaluated. Many of them will likely stay changed and will probably never be provided in the same way in post-pandemic reality. The COVID-19 crisis is still ongoing and some sources say that we should be prepared for a third wave of the pandemic. The scope of the analysis conducted in this publication is related to the healthcare sector, including services and Polish healthcare professionals' work quality during the COVID-19 crisis. The research gap, the basis for conducting new research, is the lack of clarified results analysing the quality assurance of healthcare workers during the COVID-19 pandemic. It is necessary to ask about healthcare professionals' rate of personal protective equipment quality in Polish medical facilities. The result of cluster analysis will help us to know what the clusters for variables on quality assurance of protection measures for healthcare workers are. The research was carried out using a questionnaire survey on a sample of 21 medical personnel in Polish hospitals. The main findings of this publication are problems with information flow between staff and staff managers and determining appropriate zones. The quality of the personal protective equipment offered by medical facilities' management and their availability is at an appropriate level. The publication aims to analyse the level of quality assurance of health care worker protection measures in the example of Silesian voivodeships in Poland during the COVID-19 pandemic.
Keywords: 350; cluster analysis; COVID-19; healthcare workers; personal protective equipment; personalized medicine; service quality